Reduksi Stres Caregiver Pasien Gangguan Jiwa dengan Pelatihan Manajemen Stres - Dyah Wahyuningsih; Widyo Subagyo; Mukhadiono Mukhadiono (Prodi Keperawatan Purwokerto, 2020)
Background: Preliminary survey data in Kedondong village got patients with mental disorders with a considerable number of 23 people. Psychological conditions experienced by the family feel desperate with the condition of family members who suffer from mental disorders and do not go away, feel shy, resigned, let, some shut down. The process of treatment of mental patients will be more conducive if caregiver is able to manage the stress experienced in caring for mental patients. For that, stress management training is very important for caregiver. Research method: The purpose of this study was to determine the effect of stress management training on stress caregiver for mental patients. The research design is